AN INVESTIGATION INTO HUMOR LINGUISTIC STRATEGIES IN ENGLISH SPEECHES IN THE ONLINE CHANNEL OF TED TALKS FROM PRAGMATIC PERSPECTIVES - Châu Bách Nhã (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study has been carried out in an attempt to examine the most humor strategies adopted in English speeches in TED TALKS. The data of the study were collected from 100 English speeches in random from TED TALKS. Thirteen segments were chosen to be analyzed in detail in terms of humor strategies. Under qualitative and quantitative approaches, the data were described and analyzed on humor strategies and violating Maxims of Grice’s Cooperative Principle in order to yield more precise points on humor strategies in English speeches in TED TALKS. On a close analysis, the thesis tried to find out some frequently used humor strategies which stems from flouting or violating Grice’s Cooperative Principle. The results demonstrate a close relationship between humor and the violation of Grice’s Cooperative Principle. It is obvious to see that violating or flouting Maxims of Grice’s Cooperative Principle created humorous situation. The speakers in TED TALKS took advantage of various humor strategies to cause laughter or amuse the listeners. With the hope of contributing to better teaching and learning English as a foreign language, especially to better the awareness of learners in understanding and making an impressive speech by using their sense of humor, some suggested ideas were also included. As for learners, theoretically, it equips them with some basis knowledge of the nature of humor. These English speeches contain humor strategies which are used in reading and listening skills . This gets attention from the audience more effectively. English learners should recognize the humor strategies that the speakers use to apply humor in their daily conversation or in English speeches. Moreover, English learner can make a suitable choice of humor strategies to communicate effectively.Humor is one of the most difficult aspects in making an effective speech in front of the audience. Therefore, handling the knowledge of humor and applying humor is a challenge.